1,2,4-Triazoles from 1,3-Dipolar Cycloaddition Reaction of Nitrilimines with Aliphatic Ketohydrazones Carrying Electron Withdrawing Groups - M. Awadallah, Adel; A. EL-Sawi, Emtithal; S. Ferwanah, Abdel-Rahman; M. Dalloul, Hany (Asian Journal of Chemistry, 2010)
Alkanone and cycloalkanone hydrazones (3) carrying electron withdrawing groups (OCOCH3, COCH3, COPh) react with C-benzoyl-and C-2-naphthoylnitrilimines to give the cycloaddition triazole products (6–11). IR, 1H NMR, 13C NMR and mass spectral data are consistent with the assigned triazole ring system. Compounds (8, 9) having an acetyl group, show signal doubling in their 13C NMR spectra, apparently owing to their presence in two different mesomeric structures.